86.9k views
4 votes
Expand the expression: ln 8/5x

User Mpartan
by
5.4k points

1 Answer

5 votes

Answer:


ln((8)/(5x) )=ln(8)-ln(5)-ln(x)

Explanation:

Use the properties of logarithms on each step:

First use the property for the logarithm of a quotient:


ln((a)/(b) )=ln(a)-ln(b)

So we get:
ln((8)/(5x) )=ln(8)-ln(5x)

Now, we can expand the last term using the property of logarithm of a product:


ln(a\,*\,b)=ln(a)+ln(b)

Therefore we write
ln(5x)=ln(5)+ln(x)

No we insert this result in the subtraction we had before:


ln((8)/(5x) )=ln(8)-ln(5x)=ln(8)-(ln(5)+ln(x))=ln(8)-ln(5)-ln(x)

User Pavlo Glazkov
by
5.5k points